A rat long‐lasting cystitis model induced by intravesical injection of hydrogen peroxide. Issue 4 (27th February 2017) - Dogishi, Koji; Okamoto, Ken; Majima, Tsuyoshi; Konishi‐Shiotsu, Shizuka; Homan, Takashi; Kodera, Mizuki; Oyama, Shohei; Oyama, Tatsuya; Shirakawa, Hisashi; Yoshimura, Naoki; Nakagawa, Takayuki; Kaneko, Shuji
Abstract: Novel longer lasting inflammatory bladder animal models are needed to better understand the pathophysiology of chronic cystitis. We previously developed a relatively long‐lasting mouse cystitis model by intravesical injection of hydrogen peroxide (H2 O2 ). To further evaluate its pathophysiology, in this study, we established and analyzed a rat cystitis model. Under anesthesia, 1.5% H2 O2 solution was introduced transurethrally into the bladder of female rats, and kept for 30 min. The H2 O2 injection significantly increased the number of micturition events up to day 14 and decreased urine volume per micturition, with the smallest volumes on day 3, compared with the vehicle‐treated group. Cystometric analysis on day 7 revealed that intercontraction intervals were significantly shortened without affecting the baseline, threshold, or maximum pressures. Intravesical resiniferatoxin‐evoked nociceptive behaviors, such as freezing, were significantly enhanced on days 7 and 14. Furthermore, histopathology revealed hemorrhage, edema, infiltration of neutrophils into the lamina propria, and urothelial denudation in the early phase (day 1). These damages were gradually repaired, while hyperplasia of the urothelium, vascularization, increases in fibroblast counts, and infiltration of mast cells and eosinophils were observed through the later phase (days 7 and 14). These results suggest that intravesical H2 O2 injection induces relatively long‐lasting cystitis with enhanced bladder activity and pain sensation in rats. This approach thus provides a novel rat long‐lasting cystitis model that allows us to analyze detailed symptoms and pathophysiology of H2 O2 ‐induced cystitis model than the mouse model and may be used to investigate the pathophysiology and treatment of chronic bladder hypersensitive disorders, such as bladder pain syndrome/interstitial cystitis. Abstract : Novel longer lasting inflammatory bladder animal models are needed to better understand the pathophysiology of chronic cystitis. In this study, we established and analyzed a rat long‐lasting cystitis model induced by an intravesical injection of H2 O2 . An intravesical injection of H2 O2 induces relatively long‐lasting cystitis with enhanced bladder activity and pain sensation in rats.